Last-mile logistics: Analysis of retail sector in Lima Metropolitana during the COVID-19 pandemic - Castillo Loayza, Julia; Hyldebre Mendoza, Roberto; Jara Barrera, Paola; Junco Meza, Cynthia; Paredes Arca, Luisa; Moscoso Cuaresma, Julio Ricardo; AZABACHE MORÁN, CARLOS ALBERTO (LACCEI, 2024)
Abstract– This research examines the perception of customers in Lima regarding last-mile logistics in their online retail purchases during the state of emergency caused by COVID-19. To achieve this, a mixed-methods approach was employed, consisting of 134 surveys conducted with consumers from various retail companies. In-depth interviews were also conducted with logistics experts and customers who made purchases during this period. Findings from the proposed hypotheses indicate that the current context has led to new online shopping habits among customers, revealing the emergence of new issues and the persistence of others during the online purchasing and product delivery processes.